Schizosphaerella size and abundance variations across the Toarcian Oceanic Anoxic Event in the Sogno Core (Lombardy Basin, Southern Alps) - Faucher G.; Visentin S.; Gambacorta G.; Erba E. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
Abundance and size variations of nannofossil Schizosphaerella punctulata were quantified in the uppermost Pliensbachian–Lower Toarcian succession recovered with the Sogno Core (Lombardy Basin, Northern Italy). High-resolution nannofossil biostratigraphy and C-isotopic chemostratigraphy identified the Jenkyns Event within the Toarcian oceanic anoxic event (T-OAE) interval. Absolute abundances and morphometric changes of “small S. punctulata” (< 7 μm), S. punctulata (7–10 μm; 10–14 μm; > 14 μm) and “encrusted S. punctulata” (specimens with a fringing crust) show large fluctuations across the negative δ13C Jenkyns Event. The Schizosphaerella crisis is further characterized by a decrease in average valve size in the early–middle Jenkyns Event. The abundance fall was caused by the failure of S. punctulata specimens >7 μm and “encrusted S. punctulata” that along with the increased relative abundance of small specimens, produced the reduction of average dimensions also documented in the Lusitanian and Paris Basins, although with a diachronous inception. The average valve size from the Lombardy Basin is ~2 μm smaller than in these other basins. Hyperthermal conditions associated with excess CO2 and ocean acidification possibly forced the drastic reduction of S. punctulata abundance/size. In the pelagic succession of the Sogno Core there is a strong positive correlation between the S. punctulata (> 7 μm) absolute abundance/size and the CaCO3 content, with a negligible contribution by small specimens (< 7 μm). Encrusted specimens testify selective neomorphic processes: the diagenetic crust seems diagnostic to separate S. punctulata from S. astraea.